A new generation of highly sensitive luminescent thermometers operating in the optical window of biological tissues. Issue 24 (20th May 2016) - Marciniak, Lukasz; Bednarkiewicz, Artur; Kowalska, Diana; Strek, Wieslaw
Abstract : A new type of luminescent thermometer based on highly temperature dependent d–d Cr 3+ transitions related to barely temperature dependent f–f Nd 3+ transitions for bio-application is reported for the first time, showing exceptionally high sensitivity. Abstract : A new type of luminescent thermometer based on highly temperature dependent d–d Cr 3+ transitions related to barely temperature dependent f–f Nd 3+ transitions is reported for the first time, showing exceptionally high sensitivity and shifting current paradigms behind the physics and chemistry of luminescent nanothermometers. The highest sensitivity in the physiological temperature range was found for LiLaP4 O12 :1%Cr, 10%Nd and reached 4.89%/°C – three times, up to over one order of magnitude higher than most luminescent thermometers reported to date. Moreover, the brightness of such probes based on Cr ions was around one order of magnitude higher than the Stokes Nd emission. Even higher sensitivities, up to 30%/°C, were found above 200 °C, indicating the importance of a rational approach to the design of chemical composition and smart involvement of photophysical processes, to significantly enhance the properties of luminescent thermometers. The thermal dependence of the luminescence intensity ratio from the two ions was investigated for different Cr 3+ and Nd 3+ ion concentrations, which actually had no severe impact, either on the LIR or on the sensitivity of such luminescent thermometers.